(untitled) (Bheshaja: Journal of Central Ayurveda Campus, 2025)
Vataja Unmada is a type of Unmada which can be correlated to Psychosis based on sign and symptoms of both conditions. Childhood psychosis is an extremely rare condition. In this case report, we present a case of 12 yr old male child with symptoms suggestive of psychosis and later responded well to the Ayurvedic management with Brahmi Ghrita and Saraswatharishta. This study is an effort to reveal the diagnosis of Vataja Unmada, in this case a very early onset childhood psychosis, which is challenging and yet important for the specific management of condition so as to prevent the long-term disability.